2018
DOI: 10.20960/nh.1932
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introducción: los estudios en consumo dietético infantil no se enfocan generalmente al tipo de líquidos consumidos. Objetivo: documentar los líquidos presentes en la dieta de infantes mexicanos < 1 año, participantes en la Encuesta Nacional de Salud y Nutrición 2012 (ENSANUT-2012) de acuerdo a su edad y lactancia. Métodos: se analizaron las prácticas de alimentación de infantes < 1 año de la ENSANUT-2012 en niños no amamantados (no-A) y amamantados (A) determinado por status quo para el consumo de líquidos agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
3
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
4
3
0
11
Order By: Relevance
“…The results of the PF tests showed that obese subjects presented lower values than normal weight participants on tests that required acceleration of body mass. Hence, obese subjects had lower values of CRF compared to the other groups (in both girls and boys), which is similar to the findings described in former studies [22,[39][40][41]. Similarly, these results were comparable to other studies conducted in Spain [22,42,43], as well as in the Region of Murcia [25,26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the PF tests showed that obese subjects presented lower values than normal weight participants on tests that required acceleration of body mass. Hence, obese subjects had lower values of CRF compared to the other groups (in both girls and boys), which is similar to the findings described in former studies [22,[39][40][41]. Similarly, these results were comparable to other studies conducted in Spain [22,42,43], as well as in the Region of Murcia [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…However, regarding relative muscle strength, obese participants presented inferior results than normal weight children, in both sexes. Previous studies in handgrip strength test revealed similar results to ours [39,46,47]. Similarly, lower results were found in both obese boys and girls for the standing broad jump test, as seen in other studies [39,46,47].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, decreased PA and fitness, and increased sedentary behaviors such as screen time (ST) have been associated with a cluster of behavioral risk factors and negative mental health in children (3), this being considered a new variable in child and youth health (16). Additionally, PA and fitness have been indicated as an important factor to prevent physical and mental health (17) due to is modifiable nature. So, identifying modifiable lifestyle behaviors such as MD adherence and PA patterns linked to feelings and well-being is necessary to develop preventive strategies for schoolchildren.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in relation to age, they show that this relationship is negative, i.e. the older the person, the less physical condition, which denotes non-linearity (Bauman et al, 2009;Palomino et al, 2017;Prieto Benavidez et al, 2015;Delgado -Floody et al, 2019), those that show how it is in adulthood where physical activity practice increases again and physical condition improves (Humphreys and Ruseski 2010) those that establish how BMI is closely related to diet, physical activity practice and parents' schooling (Bucco-dos Santos,& Zubiaur-Gonzales 2013;Díaz-Martínez et al, 2013;Cubidos de Carrillo, 2015;Zurita-Ortega et al, 2018;), who propose how sleep restriction is a risk factor associated with the presence of obesity (Duran et al, 2012;Reverter-Masia et al, 2017), those who mention the importance of staying active, i.e., engaging in physical activity, physical exercise and sport, and their relationship with different social and cultural aspects (Alvarez, et al, 2020) those that show that schoolchildren with physically active parents are more inclined to practice sport (Zurita-Ortega, 2018, Solis-Urra et al, 2019. Based on the above associations, it was found that the social determinants of health that predict healthy physical condition are BMI, living with the father, number of meals he consumes per day, being a beneficiary at the school restaurant and hours he sleeps at night, which are modifiable, an aspect that invites to continue insisting on processes of construction and implementation of effective nutrition programs, lifestyles and social coexistence that help improve the physical condition of schoolchildren as well as other studies suggest (Wilkinson, 2016 ;Carulla, et al, 2019;Ochoa-Martínez et al ,.…”
Section: Discussionmentioning
confidence: 99%